Apolipoprotein E epsilon 4 allele is a risk factor for familial and sporadic presenile Alzheimer's disease in both homozygote and heterozygote carriers. Issue 8 (August 1995) - St Clair, D; Rennie, M; Slorach, E; Norrman, J; Yates, C; Carothers, A
Abstract : While apoliprotein E (ApoE) epsilon 4 allele is now a well established risk factor for familial and sporadic senile Alzheimer's disease (AD), its role in the development of the rarer presenile or early onset type is controversial. Early studies showed no association; later ones found enrichment for the epsilon 4 allele in familial or sporadic types or both. We have ApoE genotyped a series of Scottish people (n = 85) with early onset AD. We find highly significant enrichment for both homozygote and heterozygote ApoE epsilon 4 allele carriers in familial and sporadic early onset AD with a pattern closely resembling that in late onset AD.